Choosing to live how to defeat suicide through cognitive therapy - Ellis, Thomas E. (New Harbinger Publications, 1996)
Counter Choosing to Live is the first self-help guide addressed to those who are considering suicide. In an empathetic nonjudgmental tone, the authors provide tools to help readers assess the risk and understand the factors that reinforce suicidal talk and behaviors. A step-by-step program for change shows how to replace negative beliefs and develop alternative skills for solving problems. For professionals who are helping seriously depressed clients, Choosing to Live offers the clear guidance of a treatment manual plus readings and exercises for clients to do at home.